The Information Content of Realized Losses - Kelly, Peter (Review of Financial Studies, 2018)
Examining the trades of company insiders, I find that a sale of stock at a loss is a much more negative signal about future returns than is a sale of stock at a gain. I consider a range of explanations for my results and find that the evidence is most consistent with the idea that investors derive direct disutility from selling a stock at a loss. Since selling a stock at a loss is painful, an investor who sells at a loss must have particularly negative information. This result offers a novel measurement of the strength of the disposition effect. Received December 7, 2015; editorial decision December 18, 2017 by Editor Robin Greenwood. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.